Proofs and Algorithms An Introduction to Logic and Computability - Dowek, Gilles; SpringerLink (Online service) (London : Springer London, 2011)
Proofs and Algorithms: An Introduction to Logic and Computability Logic is a branch of philosophy, mathematics and computer science. It studies the required methods to determine whether a statement is true, such as reasoning and computation. Proofs and Algorithms: An Introduction to Logic and Computability is an introduction to the fundamental concepts of contemporary logic - those of a proof, a computable function, a model and a set. It presents a series of results, both positive and negative, - Church's undecidability theorem, Gödel s incompleteness theorem, the theorem asserting the semi-decidability of provability - that have profoundly changed our vision of reasoning, computation, and finally truth itself. Designed for undergraduate students, this book presents all that philosophers, mathematicians and computer scientists should know about logic.
Keywords: Computer science; Information theory; Computer Science; Theory of Computation; Mathematical Logic and Formal Languages